Marketing Mix Relative to Competitiveness on Selected Lechon Manok Enterprises in Maligaya St., Novaliches, Quezon, City: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to assess the marketing mix of selected lechon manok enterprises in Maligaya St., Novaliches, Quezon City, in terms of price, promotion, place, product, people, process, and physical evidence. The study also aims to identify the problems encountered by the lechon manok enterprises in terms of assessing the marketing mix and to propose recommendations on how the lechon manok enterprises can sustain their business success.The study used a mixed-methods approach. Two groups of respondents were used: twenty-five (25) male and twenty-five (25) female customers, for a total of fifty (50) respondents. A survey questionnaire was used to collect data from the respondents. The questionnaire was designed to assess the respondents' perception of the marketing mix of the selected lechon manok enterprises.The results of the study showed that the respondents generally agreed that the marketing mix of the selected lechon manok enterprises is effective. However, the respondents did not support the statement that the lechon manok enterprises are doing enough to promote their businesses. The study also identified the following problems encountered by the Lechon Manok enterprises in terms of assessing the marketing mix: Lack of awareness of the marketing mix concept, Lack of resources to invest in marketing activities, and Difficulty in measuring the effectiveness of marketing activities.The study recommended the following to the selected lechon manok enterprises to sustain their business success: Invest in and expand their presence on social media platforms like Facebook and Tiktok, strengthen their traditional marketing efforts, such as issuing flyers and posters, consider offering discounts, promos, and coupons to attract and retain customers. The study found that the marketing mix of the selected lechon manok enterprises is generally effective. However, the lechon manok enterprises need to improve their promotion efforts to reach a wider audience. The study also recommends that the lechon manok enterprises should invest in social media marketing and traditional marketing methods to sustain their business success.
Keywords: lechon manok enterprises; marketing mix